THE IMPLEMENTATION OF TEACHING STRATEGY IN CONDUCTING SPEAKING SKILL FOR GRADE X AT SMA NEGERI 1 BADAR - Naomi Yohanna Tri Nanda; Rahmad Husein; Safrida Lubis (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2018)
This study aims to find strategies on teaching English Speaking which are suitable to the needs of students of Senior High School. The research was conducted by descriptive qualitative research through three phases; observation, interviewing and documentation. It was conducted in SMA Negeri 1 Badar, especially grade X. The data were gathered by administering interview and observation to 20 respondents to get the students’ needs. The interview and observation results prove that the teaching strategy is not implemented well and need to be improved. The average scores are the first from English lecturer and the second from English teacher. It means that the implementation of teaching strategy in conducting speaking skill as suitable or approriate for grade X of SMA Negeri 1 Badar. Key words: Descriptive Qualitative Reseach, Speaking Skill, Curriculum 2013.